Integrating Buddhadhamma Principle in Administration of Academic Excellence of Primary School in SamutPrakan Province - ปภสฺสโร, พระครูโกศลพัฒนาภรณ์; บุญปู่, สมศักดิ์; งามประโคน, สิน (Journal of Educational Review Faculty of Education in MCU, 2019)
Research Integrating Buddhist principles in the management of academic excellence of schools in Samut Prakan. purpose To study the concept and execution of academic excellence along harmonies. To study Buddhism in the management of academic excellence. To integrate Buddhism in the management of academic excellence of schools in Samut Prakan province. Study concept and execution of academic excellence along harmonies. The educational curriculum as prescribed. Media teaching art in a student-centered teaching. Teaching activities by integrating Buddhist principles to learning. And measure and evaluate authentic learning. Study of Buddhism in the management of academic excellence by using the influence of the baht in the fourth academic administration. The principles that lead to success in every subject and every activity, whether it be for work or study. Integrating Buddhist principles in the management of academic excellence of schools in Samut Prakan province. These four main influence baht apply to activities that promote learning in a student-centered learning, together with the instructor